Analisis Faktor-Faktor yang Mempengaruhi Kebijakan Dividen dengan Firm Size sebagai Variabel Kontrol (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2015) - Silaban, Christy N.; Demi Pengestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to identify the main factors influencing dividend policy proxied by Dividend Payout Ratio (DPR) especially in manufacturing companies listed on the Indonesian Stock Exchange (IDX) during period 2011-2015. The population of this research consists of 141 manufacturing companies listed on the IDX in years 2011-2015. This research used secondary data and used purposive sampling method in determining the sample. The total sample in this study are 58 companies. Multiple regression is used as the analysis technique in this research. The study documents the positive significant effect of firm size, profitability, growth opportunities, free cash flow, and insider ownership on dividend policy. Leverage is negatively significant associated with dividend policy, moreover liquidity found has no significant effect on dividend policy.